2013
DOI: 10.1016/j.physletb.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic fields in crystal manifold

Abstract: A chain-like or a 1D crystal-like universe made of intersecting membranes in extra dimensions in a Randall-Sundrum scenario is studied. A background gravitational metric satisfying the right boundary conditions is considered to study the localization of the scalar, gauge and Kalb-Ramond field. It is found that the wave function for the fields are Bloch waves. The mass modes equations are calculated allowing us to show the zero-gap mass behavior and the mass dispersion relation for each field. Finally we genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…In a separate paper we consider this and show that the generalization to p-forms in more dimensions is possible. The main result is that the gauge field can emerge from the localization of the two form in five dimensions [11]. Another aspect to consider is the generalization to a non-abelian case as in [12] or to other couplings with the field strength [13].…”
mentioning
confidence: 99%
“…In a separate paper we consider this and show that the generalization to p-forms in more dimensions is possible. The main result is that the gauge field can emerge from the localization of the two form in five dimensions [11]. Another aspect to consider is the generalization to a non-abelian case as in [12] or to other couplings with the field strength [13].…”
mentioning
confidence: 99%
“…Therefore, the result obtained by them is not generally valid. A solution to this problem was found by the present authors in [42]. We show there that the choice ∂ μ A μ = A 5 = 0, yet being valid as a particular solution, is unnecessary.…”
Section: Introductionmentioning
confidence: 55%
“…Here we must review the results found by the authors in a previous work [42]. The geometrical coupling is proposed with action…”
Section: The One Form Casementioning
confidence: 90%
See 1 more Smart Citation
“…It is important to point that in the models mentioned here the Hodge Duality is not valid since quadratic terms breaks this duality. The analysis of massive modes of p-forms has also been considered in the literature [22][23][24][25][26][27] After the work of RS several recent results have been developed based on the idea of thick membranes and its implications for brane-world physics [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The advantage of these models is that the singularity generated by the brane is eliminated.…”
Section: Jhep04(2015)003mentioning
confidence: 99%